Acquisition of Agreement Structures by Ghanaian Arabic Learners: A Processability Theory Study - Husein, Alhassan Abdur-Rahim (Al-Adab Journal, 2021)
The study investigated acquisition of agreement structures by Arabic as Foreign Language (AFL) learners in Ghana from the Processability Theory (PT) perspective. Five Arabic agreement structures at the phrasal, sentence and subordinate clause levels of PT’s processing procedures were tested in a cross-sectional study. It aimed to establish predictions about the implicational nature of the processing procedures. Data were elicited from 15 students of the University of Ghana Arabic learners who were at different proficiency levels. Grammaticality Judgment Task and Elicited Production Task were used to elicit data. The result suggested that acquisition of agreement structures by Ghanaian AFL learners develop, generally, according to PT’s predictions. While the study largely conforms to PT predictions, the behaviour of the Noun Predicative Adjective structure in the interlanguage system of participants suggests that factors other than processing constraints may be involved in the processing architecture of the L2 learners in Ghana.